2019
DOI: 10.1029/2018jc014607
|View full text |Cite
|
Sign up to set email alerts
|

Sea State Trends and Variability: Consistency Between Models, Altimeters, Buoys, and Seismic Data (1979–2016)

Abstract: Wave hindcasts of long time series (>30 years) have been instrumental in understanding the wave climate. However, it is still difficult to have a consistent reanalysis suitable for study of trends and interannual variability. Here we explore the consistency of a wave hindcast with independent observations from moored buoys, satellite altimeters, and seismic data. We use the Climate Forecast System Reanalysis (CFSR) winds to drive a wave model since extreme events are generally well captured. Unfortunately, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 52 publications
2
32
0
Order By: Relevance
“…More generally, microseismic noise analysis will not only increase the number of ocean observations but will also be very useful in validating ocean wave models worldwide (e.g. Stopa et al 2019).…”
Section: S M a S P R E C U R S O R S O F S T Ro N G S W E L L S I M Pmentioning
confidence: 99%
“…More generally, microseismic noise analysis will not only increase the number of ocean observations but will also be very useful in validating ocean wave models worldwide (e.g. Stopa et al 2019).…”
Section: S M a S P R E C U R S O R S O F S T Ro N G S W E L L S I M Pmentioning
confidence: 99%
“…While these long-term trends could be the result of external climate variability, the time-consistency of the wind field reanalysis that feed wave hindcasts remains a major issue to be solved for gaining confidence in such results (e.g. Stopa et al 2019). Nevertheless, given the significant contribution of wave-induced processes to coastal sea level, changes in the wave conditions over decadal or longer time scales will likely contribute to coastal sea level changes and need to be further investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Numerical wave hindcasts forced by General Circulation Models (GCM) or Regional Climate Model(RCM) reanalysis offer an additional alternative to study wave climate variability over a longer time period with a high resolution and global coverage, even though temporal inhomogeneity in the reanalysis data limit the confidence in the model results for long-term trends analysis (e.g Stopa et al 2019…”
mentioning
confidence: 99%
“…Further, as the impacts of global change appear to be taking place in East Antarctica faster than previously anticipated (Fox, 2019;Witze, 2018), and since both sea ice loss and ocean swell can play a part in ice shelf disintegration (Massom et al, 2018), microseism intensity may prove useful in understanding rapid changes in these interacting Earth systems. Recent use of microseism intensity for the detection of long-term climate trends by the oceanography community (Stopa et al, 2019) may be further developed using the relationships we have identified in this contribution.…”
Section: 1029/2019jf005354mentioning
confidence: 99%